Communicating About Evaluation: A Conceptual Model and Case Example - Bianca Montrosse-Moorhead; Aarti P. Bellara; Anthony J. Gambino (Journal of MultiDisciplinary Evaluation)
Background: Despite consensus within the evaluation community about what is distinctive about evaluation, confusion among stakeholders and other professions abounds. The evaluation literature describes how those in the social sciences continue to view evaluation as applied social science and part of what they already know how to do, with the implication that no additional training beyond the traditional social sciences is needed. Given the lack of broader understanding of the specialized role of evaluation, the field struggles with how best to communicate about evaluation to stakeholders and other professions.